TRUMP’S ELECTED SHOCK EFFECT IN INDONESIAN STOCK MARKET - Sagita, Vietha Devia (Journal of Indonesian Applied Economics, 2017)
It is inevitable that the presidential election in the United States can caused stock market fluctuations both in the United States alone as well as in other countries, for example Indonesia. Using regression method and chow test this study aimed at the effects before and after the election of Donald Trump as president of the United States on November 8, 2016. Using the data series shares the value of DJIA and ICI, this study analyzes the emergence of shock due to the change of president in United Staten share prices at the stock market in Indonesia. Based on the chow test result, the election of Donald Trump can provide a shock effect on ICI as well as DJIA, because the value of 6.917956 F count is larger than the value of 3,93 F table. DJIA positive influence on the value of ICI shares due to the election of Donald Trump is significantly below 5% at 1855.782. Meanwhile, before the election of Donald Trump DJIA has a negative influence on the ICI for - 1407.59. Based on that we can conclude that the election of Donald Trump bring a good impact on the growth of the Indonesian stock market.